Solution of nondifferentiable optimization problem for object with distributed parameters based on quasi-asymptotic approximate model - N. V. Diligenskiy; A. P. Efimov (Vestnik Samarskogo gosudarstvennogo tehničeskogo universiteta. Seriâ Fiziko-matematičeskie nauki, 2011)
The possibility of approximate quasi-asymptotic models application is considered on an example of the solution of a time-optimal heating problem. To solve an optimal control problem the numerical algorithm has been used on the basis of spline extrapolation of the minimized field at each iteration. It is shown that this approach to the time-optimal control problem can provide with negligible error the determination of maximum admissible accuracy and interval durations for one-, two-, and three- stage control.